Мировой финансово-экономический кризис как детерминанта внешнеполитической стратегии КНР - Шевчук, Александр В. (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper discusses the current financial and economic crisis as one of the determining factors of the foreign policy of the People’s Republic of China. The author contemplates what influence the crisis may exert on the global balance of power. As regards the future global position and role of China, he refers to the opinions and prognoses of researchers and experts in international relations such as R. D. Kaplan, Z. Brzezinski, G. Friedman, H. Kissinger, J. Nye Jr. and others, showing the issue in a broader, geopolitical context.
Global financial and economic crisis as the determinant of the foreign strategy of the People’s Republic of China